2003
DOI: 10.1080/1350176032000046912
|View full text |Cite
|
Sign up to set email alerts
|

Political parties, institutions, and the dynamics of social expenditure in times of austerity

Abstract: The containment of social expenditure growth has been (and still is) a core issue of public policy in advanced industrial countries since the 1980s and has received much academic attention during that period. Among the most extensively discussed explanatory factors of social expenditure are partisan politics and political institutions, as well as the dependency of the real impact of the former on the latter. The paper distinguishes five competing theoretical perspectives and explores their power to explain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…A rising unemployment rate is likely to increase social spending (Snyder and Yackovlev 2000;Kittel and Obinger 2003;Avelino et al 2005). Avelino et al (2005) argue that even if there are few unemployment programs in Latin America, there should be a positive relationship between unemployment and social spending, due to governments' efforts to counteract the negative effects of any crisis and to promote employment generation.…”
Section: Economic Determinants Of Social Spendingmentioning
confidence: 99%
See 1 more Smart Citation
“…A rising unemployment rate is likely to increase social spending (Snyder and Yackovlev 2000;Kittel and Obinger 2003;Avelino et al 2005). Avelino et al (2005) argue that even if there are few unemployment programs in Latin America, there should be a positive relationship between unemployment and social spending, due to governments' efforts to counteract the negative effects of any crisis and to promote employment generation.…”
Section: Economic Determinants Of Social Spendingmentioning
confidence: 99%
“…Studies on the determinants of social spending have increased since the late 1970s, coinciding with the implementation of social policy reforms carried out in developed countries to strengthen their welfare states (Kittel and Obinger 2003). Several determinants of social spending were considered, such as the ideological orientation of governments, integration into global markets or the degree of fiscal decentralisation.…”
Section: Determinants Of Social Spendingmentioning
confidence: 99%
“…This new politics of welfare has been accepted by many researchers (Busemeyer 2009;Castles 2007;Huber and Stephens 2001;Kittel and Obinger 2003;Zohlnhöfer et al 2008). For instance, Schneider, Fink, and Tenbücken (2005) studied the changes in the shares held by the government of the dominant provider in three infrastructure sectors (telecommunications, electricity, and aviation sectors) between 1970 and 2000, and they found that partisan differences seen in the 1980s disappeared in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the difference thesis, the convergence theory claims that partisan politics have converged as a result of either structural changes such as ageing or free movement of labour and economic resources, globalisation, and ideational reasons (Huber and Stephens 2001;Kittel and Obinger 2003;Pierson 2001). …”
mentioning
confidence: 99%
See 1 more Smart Citation